The right to good administration and the administrative inaction: a troubled relationship - Bonomo, Annamaria (Diritto Pubblico Europeo - Rassegna online, 2019)
Right to good administration in European law represent an umbrella principle that involves many rights for individuals dealing with public institutions and bodies. Article 41 of the Charter of fundamental rights of the European Union includes in its non-exhaustive enumeration the duty to take a decision in a reasonable time limit. As it is well known, „good‟ decision is a prompt and certain decision and a good administration is an institution that timely respond to the applications of its citizens. Leaving a person in the ignorance on the dossier outcome is a typical device of supremacy of one subject over the other. To this end, this paper aims to analyze the implementation of the right to good administration in Italian legislation with regards to one of its most significant element: the right to have a timely decision from public administration. Despite the various remedies provided in different stages by Italian legislator against administrative inaction, mostly through the i.e. tacit consent institute, nonetheless when discretionary measures are involved this mechanism seems not in line with the fundamental right to good administration that instead requires for persons affected by the administration‟s activities to have an express act in due time. A written, explicit measure definitively rests the best way to vanish doubts about the existence of a decision and uncertainties around its motivations.